QTL mapping of grain quality traits from the interespecific cross Oryza sativa x O. glaberrima - Aluko, G.K.; Martínez Racines, César Pompilio; Tohme, Joseph M.; Castaño Rodríguez, C.; Bergman, C.; Oard, J.H. (Springer, 2004)
International rice export markets are increasing demands for rapid improvements in grain quality characteristics. The African rice Oryza glaberrima is a new potential source of genes that will enhance the eating, cooking, and milling properties of the rice grain. The objective of this research was to identify and characterize quantitative trait loci (QTLs) among 312 doubled haploid lines derived from the BC3F1 of an interspecific cross of O. sativa × O. glaberrima. Genetic material was planted in replicated plots and evaluated for ten grain quality traits in 2001 in Colombia. A linkage map was constructed with 100 polymorphic microsatellite markers using the mapdisto software program to adjust for segregation distortion. Transgressive segregation was observed for all traits. Interval and composite interval analyses identified 27 QTLs for nine characters located on 11/12 chromosomes. The chromosomal positions of QTLs for percentage amylose, alkali-spreading score, and percentage protein were in agreement with data reported by others, whereas QTL markers for percentage head rice, percentage milled rice, percentage protein, and percentage brown rice were different in our mapping population. Five major QTLs were found to be associated with improved percentage rice bran, percentage amylose, and alkali-spreading score. Seven QTLs for improved percentage rice bran, percentage milled rice, alkali-spreading score, percentage protein, and grain length/width ratio were derived from the O. glaberrima accession. Three new QTLs for percentage rice bran are reported here for the first time. Results from this study suggest that the African rice might be a valuable new source for introgression and improvement of several traits that affect quality traits demanded by the different rice export markets.